Observational cohort study of a group-based VR program to improve mental health and wellbeing in people with life-threatening illnesses - Hannes Kettner; Hannes Kettner; David R. Glowacki; David R. Glowacki; Justin Wall; Justin Wall; Justin Wall; Robin L. Carhart-Harris; Robin L. Carhart-Harris; Leor Roseman; Leor Roseman; Joseph L. Hardy; et al. (Frontiers in Virtual Reality)
IntroductionBeing diagnosed with a life-threatening illness (LTI) is often accompanied by feelings of fear, uncertainty, and loneliness that can severely impact mental health. Relatively few interventions are available to address the existential concerns of individuals facing LTI, while treatment of the underlying physical ailment typically remains the priority of the healthcare system. Research has shown that psychedelic-assisted psychotherapy (PAT) holds promise for supporting mental health in people with LTIs. However, PAT’s potential in this population remains curtailed by several limitations, including regulatory and accessibility issues. Novel approaches that could provide some of the benefits of psychedelic experiences, while avoiding associated challenges, would therefore be highly desirable for supporting the mental wellbeing of people with LTIs. Among such interventions, virtual reality (VR)-based experiences have been suggested as a promising candidate. We here evaluate a program that includes weakly representational, multi-user VR experiences based on a design aesthetic previously described as “numadelic,” which has been demonstrated to elicit self-transcendent experiences comparable to psychedelics.MethodsA prospective cohort study design was used to assess the effects of “Clear Light” (CL), a group-based, 6-session multimedia program that included VR experiences, video calls, and text chats spanning 3 weeks. Participants were individuals suffering from LTIs that self-selected to participate in the CL program. A total of N = 15 participants were evaluated based on assessments 1 week before and after the program, using self-report measures of anxiety, depression, wellbeing, and secondary psychological outcomes.ResultsThe intervention was well-tolerated among participants. Significant improvements with moderate effect sizes were observed on self-reported measures of anxiety, depression, and wellbeing. Secondary measures assessing demoralization, connectedness, and spiritual wellbeing also showed significant improvements.DiscussionThis observational study demonstrated the feasibility and potential benefits of a group-based VR program that can be delivered at-home to people suffering from LTIs. While conclusions are presently limited by the lack of randomization or a comparison group, our findings strongly suggest further research is warranted, including randomized controlled trials.